Konseling Lintas Budaya Pada Kasus Kesulitan Asertif: Studi Kasus SH dalam Konteks Budaya Jawa - Padilatu Ilmi Nasution; Fadhilla Yusri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the effectiveness of cross-cultural counseling in addressing adjustment difficulties in subject NA within the context of Malay and Minangkabau cultures. The study uses a single-subject experimental approach with cognitive restructuring intervention and assertive communication training based on the behavioral approach to improve the subject’s social adaptation skills. Data were collected through in-depth interviews with NA, a second-semester student at UIN Sjech M. Djamil Djambek Bukittinggi who comes from Riau with a Malay cultural background. The results show that NA’s adjustment difficulties cannot be separated from the differences in language and communication patterns between Malay and Minangkabau cultures in the boarding house environment. The use of the Minangkabau language by roommates that NA did not understand created communication barriers, confusion, anxiety, and overthinking. Misunderstandings regarding the cleaning schedule and the accusation of taking a friend’s lipstick further strengthened NA’s feelings of being distrusted, less accepted, and tending to withdraw from the social environment. The cross-cultural counseling intervention applied integrated humanistic, cognitive, and behavioral approaches while still respecting the differences between Malay and Minangkabau cultures. The findings show that cross-cultural counseling helped NA understand that the use of the local language by roommates was a communication habit, not an attempt to mock her. Through cognitive restructuring, NA was able to replace negative thoughts with more rational ones, while assertive communication training helped NA express feelings and reduce withdrawal behavior. Based on these results, the effectiveness of cross-cultural counseling is determined by the counselor’s cultural awareness, openness to diversity, and the selection of relevant techniques such as cognitive restructuring and assertive communication training. Recommendations for NA include practicing positive thinking, gradual assertive communication, independent emotion monitoring, and periodic evaluation to achieve better adaptation in a multicultural environment.